Investment facilitation in the WTO: The case for early harvesting - Bernard M. Hoekman; Petros C. Mavroidis (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
The benefits of an Investment Facilitation for Development Agreement need not wait for ratification by all signatories or approval from all WTO members. Early implementation can be realized through provisions in signatories' GATT and GATS commitment schedules.
Keywords: 330